ANALISIS GAYA KOMUNIKASI POLITIK GUBERNUR JAWA BARAT DEDI MULYADI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze Dedi Mulyadi's political communication style in the public sphere and understand how it shapes his political image and emotional connection with the public. In the digital era, political communication is not only concerned with conveying policy messages but also involves symbolic, cultural, and emotional strategies that can build leadership legitimacy. Dedi Mulyadi is known as a political figure who integrates local Sundanese cultural values ​​into his political communication practices, through the use of regional languages, cultural symbols, and social narratives disseminated through social media. This study uses a qualitative approach with descriptive analysis methods to examine the verbal and nonverbal communication dimensions of Dedi Mulyadi's political communication style. Data were obtained through literature review, document analysis, and observation of public communication content delivered through mass media and social media. The analysis was conducted by interpreting the forms of political messages, cultural symbols, and communication strategies used to build relationships with the public. The results indicate that Dedi Mulyadi's political communication style is characterized by humanism, symbolism, and adaptability to developments in digital media. The use of local language, traditional Sundanese attire, and a personal and emotional communication approach fostered psychological closeness with the community. Furthermore, the use of social media as an interactive communication platform strengthened his image as a responsive and inclusive leader. These findings suggest that integrating local cultural values ​​and digital communication strategies can be an effective tool in building a leadership image and enhancing political legitimacy at the regional level.